Reduction of blood loss by restoration of platelet levels using fresh autologous blood after cardiopulmonary bypass - Wagstaffe, J. G. (1972)
Two methods of taking off two units of blood before bypass, storing it at 4° C, and giving it after heparin reversal at the end of bypass are described and compared. When the blood was taken into acid citrate dextrose before the patient was heparinized, the platelet count increased by 22,000/mm(3) and blood loss was reduced by 26·7% (a significant decrease). Blood, taken after heparin was given, gave a similar platelet increase after retransfusion but the resulting decrease in blood loss was 17·6% (a non-significant decrease). Neither difficulties nor complications were noted using the technique in 38 patients.